Comparative Activity of Deet and AI3-37220 Repellents Against the Ticks Ixodes scapularis and Amblyomma americanum (Acari: Ixodidae) in Laboratory Bioassays. Issue 2 (10th October 2014) - Carroll, J. F.; Solberg, V. B.; Klun, J. A.; Kramer, M.; Debboun, M.
Abstract : The repellents N, N -diethyl-3-methylbenzamide (deet) and racemic 2-methylpiperidinyl-3-cyclohexene-1-carboxamide (AI3-37220) were evaluated using two different laboratory bioassays to determine their relative effectiveness against host-seeking nymphs of the blacklegged tick, Ixodes scapularis Say, and the lone star tick, Amblyomma americanum (L.). In a petri dish bioassay, ticks were released within a ring of repellent on a horizontal filter paper disk. In the second bioassay, ticks were allowed to climb a vertical strip of filter paper whose central portion was treated with a repellent. Deet and AI3-37220 were more effective against I. scapularis than A . americanum nymphs. In the petri dish bioassay, none of the concentrations of deet or AI3-37220 tested confined A. americanum within the treated ring. However, in the vertical bioassay, both species exhibited avoidance of the repellents, and I. scapularis was repelled by much lower concentrations than A. americanum . I. scapularis were repelled by lower concentrations in the vertical bioassay than in the petri dish bioassay. Deet was slightly more effective against I. scapularis than AI3-37220 in both bioassays, but AI3-37220 was significantly more effective than deet against A. americanum in the vertical bioassay.